Über das geltende Haftungsrecht in der Chirurgie: grundsätzliche juristische Vorgaben und klinische Bezugspunkte am Beispiel der Viszeralchirurgie - Theuer, Dieter; Mieth, Markus; Büchler, Markus W. (Der Chirurg, 2012)
The spectacular increase in liability processes in the field of surgery and in particular in visceral surgery, necessitates an objectification of the conflict between surgical medical professionals and medico-legal institutions, firms of solicitors and courts. Out of court settlements assisted by expert opinion commissions of the Medical Council can avoid many legal conflicts. For improvement of the legal standpoint of a defendant medical professional an unambiguous, extensive and detailed documentation of medical examination findings, the indications for the planned operative intervention, extensive and detailed documentation on disclosure and informed consent of the patient for the planned operative intervention, an extensive, detailed careful and responsibly guided report of the operation as well as a systematic, orderly well-planned postoperative complication management are necessary to counter the accusation of an organizational failure of medical professionals and the accused hospital. The mutual building of confidence between surgical medical professionals and legal institutions is safeguarded by a comprehensive documentation and an unambiguous description and formulation of the medical discharge report on termination of inpatient treatment.